Organizational citizenship behavior pada karyawan: Adakah peranan servant leadership? - Anggraeni, Lucky Nurul; Diah Sofiah; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine whether there is a relationship between perceptions of servant leadership and organizational citizenship behavior (OCB) among PT XL Axiata employees. The subjects in this study were 52 respondents who worked at PT X in Surabaya. The research design used is a quantitative approach that aims to find out that there is no relationship between the research variables. The sampling technique used in this study is a non-probability sampling technique using incidental sampling, namely a sampling technique based on chance, that is, anyone who accidentally or incidentally meets the researcher can be used as a sample. Analysis of the data in this study using the Spearman-Brown correlation with the help of the SPSS version 26.0 program obtained a correlation score of 0.794 with a significance of p=0.000 (p<0.05). So it can be concluded that there is a significant positive correlation between the servant leadership of PT X staff and the OCB variable. That is, the higher the Servant Leadership of an individual, the higher the OCB performance. Keywords: Employee, OCB, Servant Leadership